Awanggan the Philippine e-gaming facility - Velasquez, Jansen Gabriel B. (College of Architecture, University of the Philippines Diliman, 2016)
E-sports is an industry that has grown fruitfully throughout the years. Through the past decade, gamers from all over the world have risen above the usual standards of gaming. It has elevated into a new level of proficiency by which needs of a new avenue for growth and development. To help that cause, new facilities must be created in order to re-establish the true meaning of the industry and bring about its value among all people. In the local setting, e-sports has yet to develop. Familiarity and support must be developed in order to truly create an honorable place in the local industries of the country. Philippines is one of the top contending countries in e-sports in Asia. To develop that, people need facilities that would help work, play, develop and promote the value of e-sports in local setting.